ANALISIS KINERJA ROOM ATTENDANT DALAM PENYEDIAAN LINEN DI CEMPEDAK PRIVATE ISLAND - Takaendengan, Mita Erdiaty; Rumondor, Efrat Mantiri; Bawole, Merryany Theovanny; Kumaat, Hendry M.E. (PolimdoSains, 2025)
Laundry section is an area that supports Cempedak Private Island’s operations who is in charge of washing everything linen the one in the hotel. Laundry section whose working area is different from mainland Cempedak Island, has a main focus on linen services for Room Attendant hotels are sent to the island every day. This difference in work areas results in operational problems room attendant on the island becomes less efficient due to limitations in handling parstock linens and storage linen in Cempedak Private Island for daily hotel operational activities. This research aims to find out how the rotation system works linen (Room linen) on Cempedak Private Island, to find out what obstacles exist in linen management (Room linen), to find out efforts to deal with problems in linen management. The research method used in this research is a qualitative descriptive method. Qualitative plays an important role in obtaining and managing data. Data is presented in descriptive form where this approach focuses on in- depth explanations and descriptions of the phenomena being studied. The data taken is in the form of text and narrative which can provide broader insight into the research topic. The research results prove that, role laundry section in a hotel it will be moreefficient if it uses machine power and requires attention from hotel management in providing work support facilities. The obstacles in providing linen supplies on Cempedak Private Island are the existence of laundry sections on different islands, limited equipment and limited manpower.